Metode Pengembangan Soft Skills Mahasiswa Universitas Darussalam Gontor - Damanhuri Damanhuri (At-Ta'dib, 2018)
This research is aimed to know the method of University of Darussalam Gontor to develop student’s soft skill and to know the factors that support and hinder the development of soft skills of students methods Unida Gontor Mantingan. This research included in the qualitative study with extending the data collected as scope for this study and field for this research (field research).The characteristic from the study more closer toward on study cases, because the object of its research, UNIDA students in the Business Management Faculty on Management Program in Mantingan Campus. Data collected by using a documentation technique, observation and interview. All the data that has been collected by regulated techniques, tried to sorted, grouped and categorized so that it can be found the theme in accordance with the development soft skills methode for UNIDA students. Based on the results of the researchers analyses concluded that method which are applied in soft skills development on unida students is briefing, the assignment, training, habituation, exemplary, escort and humanity. with the humanity approach, program and idialisme. So the students ready to face life in communities. While the supporting factors, is independence, a strong leadership, environmentalists who support advisory, and infrastructure and their partnership with various institutions. The resistor factors including the lack of awareness of some students of the importance activities held by UNIDA which is in the classroom, dormitory and society.